RELASI PEREMPUAN DAN ALAM DALAM LEGENDA RAKYAT SUMATERA SELATAN - Septriani Septriani; Tomi Arianto (IdeBahasa, 2022)
Malay ethnicity has a wide cultural diversity. One of them is reflected in the legend story. Legend is part of an oral story tradition that is passed down from generation to generation and is believed to be true. In legends, it is often accompanied by abstinence taught from the older generation to the younger generation for generations. This article presented a gender relation in a continuity relationship with nature contained in folk legends in the South Sumatera region. This research departed from the concept of Ecocritic Garrard (2004) and Glothfelty (1996) in looking at the relationship between humans and nature then the Ecofeminism approach (Shiva, 2005) in looking at the relationship between women and nature. The method used in this research is a qualitative method with literature study data collection techniques. The analysis was carried out using interpretative descriptive analysis techniques. In this research, researchers analyzed three South Sumatera folk legends entitled Legend of Putri Kembang Dadar, Putri Kemarau and Antu Banyu. The results of this study indicated that the legend of South Sumatra region represented and narrated a gender perspective that put women as the central life of nature. Even though there are discriminatory discourses about women's space and power, in continuity women's discourse is always strong and attached to natural life.